Electrochemical oxidation of ochratoxin A at a glassy carbon electrode and in situ evaluation of the interaction with deoxyribonucleic acid using an electrochemical deoxyribonucleic acid-biosensor - Oliveira, S. C. B. (2007)
Ochratoxin A (OTA) is a fungal metabolite that occurs in foods, beverages, animal tissues, human blood and presents carcinogenic, teratogenic and nephrotoxic properties. This study concerns the redox properties of OTA using electrochemical techniques which have the potential for providing insights into the biological redox reactions of this molecule. The in situ evaluation of the OTA interaction with DNA using a DNA-electrochemical biosensor is also reported.